Investigation of vanet performance in the presence of sinkhole attack and timing attack - Nazir, Fahad (School of Computer and Communication Engineering, 2016)
The scope of this thesis is limited to the evaluation of VANET performance in the presence of Timing attack and Sinkhole attack. The security attacks in VANET and its security issues, such as the impact on its practice is also presented. Attacks in VANET are directly effected by network performance. As it is a matter of security risks therefore, this thesis work can be considered as an evidence of network performance in the presence of Timing attack and Sinkhole attack.